A microstructure-level study of monoglycerides oleogels using rheomicroscopy - Palla, Camila Andrea (2017)
Monoglycerides oleogels are semisolid systems containing self-assembled structures formed by crystalline material entrapping liquid oil in a three-dimensional network. The microstructure of the network of these oleogels determines their macroscopic functionality. Interestingly, these oleogels can be tailored by modifying the preparation conditions and, in particular, the cooling rate.In this work, the effect of the cooling temperature profile (CTP) employed in the production of oleogels from monoglycerides and high oleic sunflower oil was investigated using a torsional rheometer equipped with a polarized optical microscope. This technique allows simultaneously carrying out rheological measurements and recording images of the internal structures of the gels during the gelation process. With this, it becomes also possible to obtain microstructural parameters such as the Avrami index that allows us to determine the dimensionality of the crystal growth process. Once the gelation processed finished, the microstructure of the oleogels was also analyzed by confocal and optical microscopy. Micrographs were processed and analyzed using ImageJ software in order to estimate the fractions of solid crystalline and oil, and to determine the network characteristics such as the crystal length and shape, and the box-counting fractal dimension. Micrographs obtained using these three complementary microscopic techniques revealed a strong consistency. Generally speaking, monoglycerides crystal aggregates distribute in irregular, elongated, fibrillar or needle-like shape. The analysis of the distribution of crystal sizes resulted in very similar median values, D50, which rose with the increase of the CTP. The highest CTP allowed to obtain oleogels with the highest elastic modulus, a fractal dimension close to 2 and a solid crystalline fraction of about 0.15.